DEVELOPMENT OF MATHEMATICAL METHODS AND ALGORITHMS FOR CREATING AN INTELLECTUAL SYSTEM OF TARGETED ACCOMMODATION OF THE HIGHER EDUCATION OF THE INSTITUTIONS - Abduvalieva Zebinuso (Scholar Express Journal, 2021)
The development of computer technology provides great opportunities for modernizing the learning process. Many new concepts have entered modern practice: a single educational space, a single educational information environment, a virtual university, massive open online courses.
Keywords: Educational information environment; virtual university; unified educational space; massive open online courses.